2016
DOI: 10.1111/anec.12413
|View full text |Cite
|
Sign up to set email alerts
|

Minimal T-wave representation and its use in the assessment of drug arrhythmogenicity

Abstract: The minimal T-wave representation can potentially be used as a new tool to identify normal from abnormal repolarization in drug safety studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Interestingly, our recent work has proposed the minimal T-wave representation by making T-wave independent of QT duration and thus much less dependent on heart rate. The results of analyzing the minimal T-wave shape showed that it could identify normal from abnormal repolarization significantly better compared to heart rate corrected QT interval (QTc) and most of the prolongation occurred in the ascending segment of the T-wave whereas T-peak to T-end was less sensitive relatively after d,l-sotalol [38]. Also, studies of the effects of some IKr blockers on multiple sub-intervals of the QT interval showed that hERG potassium channel block equally affects the whole T-wave duration, early and late repolarization (Tj to Tend and Tpe intervals) whereas additional inward current block (calcium or late sodium) preferentially shortens early repolarization [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our recent work has proposed the minimal T-wave representation by making T-wave independent of QT duration and thus much less dependent on heart rate. The results of analyzing the minimal T-wave shape showed that it could identify normal from abnormal repolarization significantly better compared to heart rate corrected QT interval (QTc) and most of the prolongation occurred in the ascending segment of the T-wave whereas T-peak to T-end was less sensitive relatively after d,l-sotalol [38]. Also, studies of the effects of some IKr blockers on multiple sub-intervals of the QT interval showed that hERG potassium channel block equally affects the whole T-wave duration, early and late repolarization (Tj to Tend and Tpe intervals) whereas additional inward current block (calcium or late sodium) preferentially shortens early repolarization [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…These two state-of-the-art methods also indirectly aid in uncovering dependencies. In connection with such a statement, the same case is applied These components are integrated to produce Semitics of TS through both intra-coupling and inter-coupling relationships within a set of behaviors [56]. The Behavior Constraint Indicator module formalizes natural language descriptions of behaviors into logical formulas.…”
Section: Rq4: Dependencies Impact Of the T Wavementioning
confidence: 99%
“…R-on-T, which may lead to torsade de pointes type of arrhythmia 23 . Another important research direction concerning repolarization is drug arrhythmogenicity assesment 24 .…”
Section: Introductionmentioning
confidence: 99%